2016
DOI: 10.1371/journal.pone.0164780
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Schedule for Urban Road Network Repair Based on the Greedy Algorithm

Abstract: The schedule of urban road network recovery caused by rainstorms, snow, and other bad weather conditions, traffic incidents, and other daily events is essential. However, limited studies have been conducted to investigate this problem. We fill this research gap by proposing an optimal schedule for urban road network repair with limited repair resources based on the greedy algorithm. Critical links will be given priority in repair according to the basic concept of the greedy algorithm. In this study, the link w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…Recently new domains of evolutionary algorithms have emerged to handle Wind Farm applications. Among all the algorithms presented in the previous section, the greedy algorithm [5] , [121] stands tall in terms of convergence value and It is noteworthy to mention that theoretical error in this method is 0.0001%. In the evolution algorithm [65] the convergence characteristics are achieved in very less generations and very minimum computational effort.…”
Section: Critical Evaluation Of Existing Research Methodologies Used mentioning
confidence: 98%
See 2 more Smart Citations
“…Recently new domains of evolutionary algorithms have emerged to handle Wind Farm applications. Among all the algorithms presented in the previous section, the greedy algorithm [5] , [121] stands tall in terms of convergence value and It is noteworthy to mention that theoretical error in this method is 0.0001%. In the evolution algorithm [65] the convergence characteristics are achieved in very less generations and very minimum computational effort.…”
Section: Critical Evaluation Of Existing Research Methodologies Used mentioning
confidence: 98%
“…According to procedural and implementation complexity the following soft computing wind farm optimization layouts techniques are ranked. (1) Multilevel extended pattern search algorithm [11] (2) Greedy Algorithm [5] , [121] (3) Ant Colony algorithm [58] (4) Quadratic Interpolation Optimization [90] (5) Particle Swam optimization [53] (6) Binary Particle Swarm Optimization [54] (7) Genetic Algorithm [2] , [112] (8) Definite Point Selection [91] (9) Evolutive algorithm [92] (10) Random Search [93] (11) Simulated Annealing [94] .…”
Section: Critical Evaluation Of Existing Research Methodologies Used mentioning
confidence: 99%
See 1 more Smart Citation
“…They used greedy algorithm to retrieve the network after the crisis. The results have shown that this method is the most effective solution for identifying the critical links on the network [16].…”
Section: An Overview Of the City Of Isfahanmentioning
confidence: 95%
“…Khademi et al studied a postearthquake response and determined the optimum route for cars in the network [15]. Lu et al (2016) planned to rebuild the urban road network caused by rain, snow and other adverse weather conditions, traffic accidents and the daily urban network conditions. They used greedy algorithm to retrieve the network after the crisis.…”
Section: An Overview Of the City Of Isfahanmentioning
confidence: 99%